2014
DOI: 10.1002/ccd.25485
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the resolute zotarolimus‐eluting stent in small vessels

Abstract: When used for the treatment of small vessels, the R-ZES appears to provide acceptable clinical results at 2 years when compared to its performance in large vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
2
19
1
Order By: Relevance
“…Consequently, for this study we used RVD ≤2.5 mm to define SV‐PCI . Similar to prior reports, we observed that patients undergoing SV‐PCI were more likely to be older, female and present with a greater burden of cardiovascular risk factors, particularly diabetes mellitus and hypertension . It is, therefore, not surprising that SV‐PCI patients in our study also presented with more coronary lesions and greater vessel tortuosity.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consequently, for this study we used RVD ≤2.5 mm to define SV‐PCI . Similar to prior reports, we observed that patients undergoing SV‐PCI were more likely to be older, female and present with a greater burden of cardiovascular risk factors, particularly diabetes mellitus and hypertension . It is, therefore, not surprising that SV‐PCI patients in our study also presented with more coronary lesions and greater vessel tortuosity.…”
Section: Discussionsupporting
confidence: 81%
“…In the era of bare metal stents (BMS) and first‐generation DES, a RVD ≤3 mm has often been used as cut‐off . However, in more recent years, as smaller stent diameters have become available, lower thresholds for RVD (e.g., <2.75 mm or ≤2.5 mm), have more frequently been used to define small vessel PCI . Consequently, for this study we used RVD ≤2.5 mm to define SV‐PCI .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the lack of direct long‐term comparative studies of DCB versus new generation DES for SVD treatment, we compared the 4.7–10.1% 2‐year TLF rates observed using everolimus‐ or zotarolimus‐eluting stents with the ones from our current study. These data suggest that even in the era of widespread use of new generation DES, DCBs may still have an important role to play in the treatment of de novo small CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of small vessel coronary disease has not been consistent in the literature, with several prior proposed definitions, including ≤3.0-mm 9 , ≤2.75-mm 10 and ≤ 2.5-mm [23]. Subsequent availability of 2.25-mm DES lead to the proposal of the definition of "very small coronary arteries" for coronary vessel lesions amenable to 2.25 mm-DES [10].…”
Section: Discussionmentioning
confidence: 96%